2022
DOI: 10.1002/glr2.12018
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation with native grassland soils improves native plant species germination in highly disturbed soil

Abstract: Background Grasslands are globally imperiled, facing continued threats from anthropogenic disturbances. Seeding remains a common grassland restoration method, and yet, is typically met with limited success, partially because soils of degraded systems inhibit the germination of native species. Methods We assessed the germination success of 16 native grassland species sown in soils collected from a degraded grassland converted into a nonnative warm‐season perennial grass, Bothriochloa ischaemum, and areas previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Establishing a regimented control over quality and product control of AM fungal bioinoculants is essential, as it has long been established that the reintroduction of AM fungi could be critical to the re-establishment of plant species in areas with a land use history, where the soil community is drastically altered by disturbances, such as the reclamation of mine spoils [65], abandoned agriculture [46], or recovery from invasive plant species [66]. Previous studies have shown that additions of whole soil from adjacent native ecosystems, including native AM fungal communities, are key to the establishment of native plant species [67][68][69][70][71][72]. However, acquiring soil from native ecosystems is not practical for large-scale restorations, as the collection and transfer of enough native topsoil are highly destructive to the very ecosystems we are trying to restore and protect, and these soils may not be available.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing a regimented control over quality and product control of AM fungal bioinoculants is essential, as it has long been established that the reintroduction of AM fungi could be critical to the re-establishment of plant species in areas with a land use history, where the soil community is drastically altered by disturbances, such as the reclamation of mine spoils [65], abandoned agriculture [46], or recovery from invasive plant species [66]. Previous studies have shown that additions of whole soil from adjacent native ecosystems, including native AM fungal communities, are key to the establishment of native plant species [67][68][69][70][71][72]. However, acquiring soil from native ecosystems is not practical for large-scale restorations, as the collection and transfer of enough native topsoil are highly destructive to the very ecosystems we are trying to restore and protect, and these soils may not be available.…”
Section: Discussionmentioning
confidence: 99%